Strategi Dinas Sosial Kabupaten Purbalingga dalam Pencegahan dan Penanganan Kekerasan Terhadap Perempuan dan Anak - Batubara, Reni Lestari; Suyuti, Muh Hikamudin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Violence against women and children is one of the cruelest human rights violations. So it requires handling and preventing violence against women and children. The establishment of the Communication Forum for the Prevention and Handling of Violence against Women and Children (ForKom PPKtA) is a strategy to prevent and handle violence against women and children in Purbalingga in the community, formal and non-formal education. This research uses descriptive qualitative methods designed to gather in-depth understanding systematically and thoroughly about the problem under study. This approach aims to describe the problem as a whole, ensuring accuracy and accuracy to detail. Based on the 2024 National Women's Life Experience Survey (SPHN), 1 in 4 women in Indonesia aged 15-64 years have experienced violence. Despite the rate of physical and sexual violence against women and children, 18.35% of women reported being victims of violence by someone other than their partner, with 4.44% experiencing it in the past year. In urban areas, the number who reported experiencing violence was higher at 25.23% than in rural areas at 22.45%. In urban areas, the number who reported experiencing violence was higher at 25.23% than in villages at 22.45%. Dinsosdaldukkbp3A, especially in the field of PPPA units, formed a strategy by forming a Communication Forum for the Prevention and Handling of Violence Against Children (ForKom PPKtA), where the formation of Forkom PPKta aims to build a handling system and build a prevention system.